ANALISIS PENGARUH PENYERAPAN TENAGA KERJA DAN UPAH MINIMUM PEKERJA TERHADAP JUMLAH KEMISKINAN DI PROVINSI JAWA TIMUR TAHUN 2009-2015 - Priyono, Joko; ansori, an (JEB17 : Jurnal Ekonomi dan Bisnis, 2018)
ABSTRAKThis research starts from the writer's observation on the amount of poverty in East Java Province from year to year which change, either the amount of poverty which tends to decrease or vice versa that is increase. The results of the study are, positive influence of employment absorption, and the positive influence of minimum wage of workers on the amount of poverty in East Java Province. In an effort to mendororng the decline in the number of poverty as part of the effort to prosper the community, the government needs to do equality of employment, especially in areas that have not reached by the government so that the absorption of labor can run maximally and the government also needs to conduct policies that progressive and systematic to the minimum wage of workers in order to reduce the number of poverty, especially in East Java ProvinceÂ Keyword : Labor Absorption, Minimum Wage, and Poverty